Stink bugs (Hemiptera, Heteroptera, Pentatomidae) of the Catimbau National Park, a protected area in Brazil’s largest dry forest - Brito, Lucas Cavalcanti; Grazia, Jocelia; Barão, Kim Ribeiro (Zootaxa, 2019)
The knowledge about insects of the Caatinga, the largest seasonally dry tropical forest of South America, is largely incomplete. Aiming at reducing this knowledge gap, we conducted the first inventory of Pentatomidae (Hemiptera: Heteroptera) for the Catimbau National Park and Pernambuco State. After 48h of sampling, during dry and rainy seasons, we collected 168 specimens, comprising 12 species and 10 genera of Pentatomidae. Cyptocephala alvarengai, Dichelops (Diceraeus) caatinguensis, and Tetragonotum megacephalum are apparently restricted to the Caatinga biome and represented 40% of the collected specimens in our sample. The other nine species are widespread in South America and the majority are associated with agroecosystems.